THE DETERMINATION OF KNOWLEDGE, COMPETENCE, AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT THE OFFICE OF HARBORMASTER AND PORT AUTHORITY OF BATAM THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE - Rayessandi; Chablullah Wibisono; Sarmini (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the influence of knowledge, competence, and organizational commitment on employee performance, with work motivation as an intervening variable, at the Port Authority and Harbormaster Office of Batam. The research employed a quantitative approach using path analysis on 123 respondents selected through proportional random sampling. Data were collected via questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple regression analysis, and path analysis. The findings reveal that knowledge, competence, and organizational commitment have a positive and significant effect on work motivation. Furthermore, knowledge, competence, organizational commitment, and work motivation positively and significantly affect employee performance. Work motivation was proven to mediate the relationship between knowledge, competence, and organizational commitment on employee performance. These results highlight the importance of enhancing knowledge, competence, and organizational commitment to foster work motivation and optimize employee performance.